The number of subgroups of a direct product of cyclic p-groups - Chew, Chun Yong (Charles Babbage Research Centre, 2018)
For a prime p and positive integer n, let Cp (n) and Cp (n) denote the elementary abelian p-group of order pn and the cyclic group of order pn, respectively. In this paper, we obtain an explicit formula for determining the number of subgroups of the direct product Cp (r) ×Cps where r and s are positive integers.